Titanate and titania nanotubes : synthesis, properties and applications - Bavykin, Dmitry V. (RSC nanoscience & nanotechnology, 2010)
"This exciting new book is a unique compilation of data from a wide range of chemical and spectroscopic instrumentation and the integration of nanostructure characterisation drawn from physical, chemical, electrochemical, spectroscopic and electron microscopic measurements. It fills a gap in the current nanomaterials literature by documenting the latest research from scientific journals to provide a concise yet balanced and integrated treatment of an interesting topic: titanium oxide nanostructures within the emerging and fashionable area of nanomaterials." "The book, a valuable reference point, is aimed at professionals, postgraduates and industrial research workers in nanomaterials. Readers will gain a knowledge of the methods for synthesising nanomaterials as well as an understanding of their structure and resulting physical characteristics together with a knowledge of their (existing and potential) applications."--